Hubungan Rasio Netrofil Limfosit dengan Ketebalan Dinding Diafragma pada Pasien Kritis - Haloho, Agustina Br; Sedono, Rudyanto; Sugiarto, Adhrie; Zulkifli (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
Background: The cause of weaning failure is multifactorial. One of the causes was Ventilator Induced Diaphragm Dysfunction (VIDD) due to thinning process of the diaphragm thickness. Decreased diaphragm muscle mass might occur due to inflammatory process. This study was aimed to find the relationship between neutrophil to lymphocyte ratio (NLR) with diaphragm thickness of critical patients in ICU. Methods: This was an observational analytic study from September 2018 to January 2019 in Mohammad Hoesin Hospital, Palembang – Indonesia. Ethical appoval for the study was obtained from Ethics Committee and subjects were recruited after signing the informed consents. Only 30 subjects were involved in the end of the study. About 6 mL of blood sample from cubital vein was withdrawn from each subject to measure neutrophils and lymphocytes. Patients’ diaphragm thickness was measured by using ultrasonography on 0th, 3rd, 5th day. Collected data were then analyzed with Stata 15. Results: The chi-square test showed that the relationship of NLR (neutophil to lymphocyte ratio) of the 0th day to the decrease in diaphragm thickness on the 3rd day was not significant (p = 0.254), while the decrease in diaphragm thickness on the 5th day was significant (p = 0.015). Subjects with initial NLR values >7 had a significant higher risk of having decreased diaphragm thickness compared to subjects with initial NLR values ≤7 (RR = 1.62 (0.99-2.64); p-value = 0.003). Conclusion: Neutrophil to lymphocyte ratio affected the decrease of diaphragm thickness in patients using mechanical ventilation.